TUG OF WAR: EVALUATIVE VERSUS FACILITATIVE MEDIATOR (The Pretoria Student Law Review, 2021)
Mediation can be defined as a process where a neutral third party seeks to facilitate communication between the disputing parties to help them arrive at an amicable solution of their disputes culminating in a win-win situation for the parties. Though ‘... there is no single limiting definition of mediation, in part because mediators function in accordance with different philosophies and in statistically different ways’, the most commonly accepted definitions of mediation incorporate two essential elements: ‘(1) third-party facilitation of dispute settlement, and (2) lack of third-party power to determine the resolution of the dispute.’ The central focus of mediation is based on the principle of parties’ self-determination. To further this basic principle, the role of a mediator must be well defined. Looking at mediation from a historical perspective, mediation was confined to the facilitative role of a neutral third party. Gradually, however, there came a sharp divide amongst the existing mediators as regards the scope of intervention by a mediator in the mediation proceedings. At one end of the broad spectrum of a mediator’s role, lies his or her active role as an evaluator and at the other, that as a facilitator of communication between the parties. These two positions are, however, in contrast with each other and hence, the debate as to the most suitable role of a mediator’s intervention in the process. In part II(a) of the present paper I attempt to portray the distinction between mediators and decision-makers. Because of the emergence of evaluative forms in mediation. In part II(b) I sketch the differences between the approaches taken by the facilitative and the evaluative mediators. In part III I try to indicate the dangers posed when mediators strive to put on the evaluative cloak and finally and in part IV I sum up the paper with an appropriate conclusion.
Keywords: mediation; neutral third party; disputing parties; facilitate communication; parties’ self-determination